2019
DOI: 10.1126/sciadv.aax6352
|View full text |Cite
|
Sign up to set email alerts
|

SLC36A1-mTORC1 signaling drives acquired resistance to CDK4/6 inhibitors

Abstract: The cyclin-dependent kinase 4/6 (CDK4/6) kinase is dysregulated in melanoma, highlighting it as a potential therapeutic target. CDK4/6 inhibitors are being evaluated in trials for melanoma and additional cancers. While beneficial, resistance to therapy is a concern, and the molecular mechanisms of such resistance remain undefined. We demonstrate that reactivation of mammalian target of rapamycin 1 (mTORC1) signaling through increased expression of the amino acid transporter, solute carrier family 36 member 1 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 38 publications
1
19
0
Order By: Relevance
“…SLC3A2/SLC7A5, in addition to SLC1A5, have also been demonstrated to promote mTORC1 activity through Gln regulation [ 126 ]. SLC36A1 (PAT1), which transports Ala, Gly and Pro, was shown to positively regulate mTORC1 activation [ 127 , 128 ]. This transporter was found to drive mTORC1 signaling and contribute to cyclin dependent kinase 4/6 (CDK4/6) inhibitor resistance in melanoma.…”
Section: Differential Regulation Of Mtorc1 By Amino Acidsmentioning
confidence: 99%
“…SLC3A2/SLC7A5, in addition to SLC1A5, have also been demonstrated to promote mTORC1 activity through Gln regulation [ 126 ]. SLC36A1 (PAT1), which transports Ala, Gly and Pro, was shown to positively regulate mTORC1 activation [ 127 , 128 ]. This transporter was found to drive mTORC1 signaling and contribute to cyclin dependent kinase 4/6 (CDK4/6) inhibitor resistance in melanoma.…”
Section: Differential Regulation Of Mtorc1 By Amino Acidsmentioning
confidence: 99%
“…Tor-S6K signalling is implicated downstream of SLC36 transporters 29,30 . Expression of a dominant-negative isoform of Tor in Ras/Src-activated cells (ras1 G12V ,Tor TED ;csk −/− ) suppressed tumour growth in HSD (Fig.…”
Section: Slc36-family Transporters Are Required For Tumour Growthmentioning
confidence: 99%
“…Consistently, we found that cyclin D3 expression is negatively correlated with Fbxl8 expression in human lymphomas and low level of Fbxl8 correlates poor overall survival for lymphoma patients, supporting our conclusion that Fbxl8-cyclin D3 axis has a critical role in regulating cell cycle and tumorigenesis. CDK4/6 inhibitors are being used for many clinical trials and the efficacy has been assessed in many types of cancers where cyclin D1 is overexpressed [24,[29][30][31]. Our data demonstrate that cyclin D3T283A accumulates in the nucleus and promotes oncogene-induced tumorigenesis in hematopoietic cells, reflecting increased CDK activity.…”
Section: Discussionmentioning
confidence: 74%
“…CDK4/6 inhibitors are being used for many clinical trials and the efficacy has been assessed in many types of cancers where cyclin D1 is overexpressed [ 24 , 29 31 ]. Our data demonstrate that cyclin D3T283A accumulates in the nucleus and promotes oncogene-induced tumorigenesis in hematopoietic cells, reflecting increased CDK activity.…”
Section: Discussionmentioning
confidence: 99%